2010
DOI: 10.1152/japplphysiol.01221.2009
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxic cutaneous vasodilation is sustained during brief cold stress and is not affected by changes in CO2

Abstract: Hypoxia decreases core body temperature in animals and humans during cold exposure. In addition, hypoxia increases skin blood flow in thermoneutral conditions, but the impact of hypoxic vasodilation on vasoconstriction during cold exposure is unknown. In this study, skin blood flow was assessed using laser-Doppler flowmetry, and cutaneous vascular conductance (CVC) was calculated as red blood cell flux/mean arterial pressure and normalized to baseline (n = 7). Subjects were exposed to four different conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
29
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 22 publications
(33 reference statements)
7
29
1
Order By: Relevance
“…Systemic isocapnic hypoxia exposure in the current investigation did not elicit the same cutaneous vasodilator response that we have observed previously (Simmons et al 2007(Simmons et al , 2010. The reason for this is that one subject in this study responded to isocapnic hypoxia with a considerable vasoconstrictor response.…”
Section: Limitationssupporting
confidence: 78%
See 1 more Smart Citation
“…Systemic isocapnic hypoxia exposure in the current investigation did not elicit the same cutaneous vasodilator response that we have observed previously (Simmons et al 2007(Simmons et al , 2010. The reason for this is that one subject in this study responded to isocapnic hypoxia with a considerable vasoconstrictor response.…”
Section: Limitationssupporting
confidence: 78%
“…Hypoxic exposure was isocapnic in this study, and we have previously demonstrated the capacity of this breathing circuit to maintain isocapnia during changes in ventilation associated with hypoxia (Simmons et al 2010). Hypoxic exposure was isocapnic in this study, and we have previously demonstrated the capacity of this breathing circuit to maintain isocapnia during changes in ventilation associated with hypoxia (Simmons et al 2010).…”
Section: Protocolsupporting
confidence: 58%
“…In a follow-up study using prolonged cooling, the magnitude of the cold-induced vasoconstrictor response was greater during hypoxia compared with normoxia, thereby eliminating the hypoxia-induced 'offset' in skin blood flow seen in the earlier (brief cooling) study (Simmons et al, 2010). Furthermore, this hypoxia-mediated increase in cold-induced vasoconstriction remained when noradrenergic receptors were blocked, suggesting that non-noradrenergic vasoconstrictor mechanisms mediate the increased cold-induced vasoconstriction during hypoxia.…”
Section: Hypoxiamentioning
confidence: 89%
“…Although the skin remained able to vasoconstrict in response to the cold stimulus, hypoxia caused a persistent vasodilatation throughout cooling, such that there was an 'offset' in skin blood flow with a similar reduction in response to cold (Simmons et al, 2010). Although the skin remained able to vasoconstrict in response to the cold stimulus, hypoxia caused a persistent vasodilatation throughout cooling, such that there was an 'offset' in skin blood flow with a similar reduction in response to cold (Simmons et al, 2010).…”
Section: Hypoxiamentioning
confidence: 99%
“…Simmons et al (46) recently showed that CVC forearm during normothermia and whole body cooling did not differ under conditions of hypocapnic and eucapnic hypoxia, which suggests hypocapnia does not affect the cutaneous vascular response in those situations. A similar result was obtained in the forearm under normothermic, normoxic conditions in the present study.…”
Section: Discussionmentioning
confidence: 99%